2022
DOI: 10.3389/fgene.2022.934920
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: DNAAF4 Variants Cause Primary Ciliary Dyskinesia and Infertility in Two Han Chinese Families

Abstract: Background: Primary ciliary dyskinesia (PCD) is a rare genetic disorder, predominantly autosomal recessive. The dynein axonemal assembly factor 4 (DNAAF4) is mainly involved in the preassembly of multisubunit dynein protein, which is fundamental to the proper functioning of cilia and flagella. There are few reports of PCD-related pathogenic variants of DNAAF4, and almost no DNAAF4-related articles focused on sperm phenotype. Moreover, the association between DNAAF4 and scoliosis has never been reported, to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The majority of them were right-handed, suggesting that the vertebral rotation is related to visceral position rather than hand use habits. Generally, patients with idiopathic scoliosis exhibit right thoracic curve and vertebrae's rightward rotation; however, in 2 studies of 4 patients with idiopathic scoliosis and situs inversus by Guo et al [9] and Lu et al, [12] the thoracic curve bent to the left and the vertebrae of mid and lower thoracic vertebrae rotated to the left in patients with situs inversus totalis, which supported that the curve direction and vertebrae rotation were mainly determined by organs distribution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The majority of them were right-handed, suggesting that the vertebral rotation is related to visceral position rather than hand use habits. Generally, patients with idiopathic scoliosis exhibit right thoracic curve and vertebrae's rightward rotation; however, in 2 studies of 4 patients with idiopathic scoliosis and situs inversus by Guo et al [9] and Lu et al, [12] the thoracic curve bent to the left and the vertebrae of mid and lower thoracic vertebrae rotated to the left in patients with situs inversus totalis, which supported that the curve direction and vertebrae rotation were mainly determined by organs distribution.…”
Section: Discussionmentioning
confidence: 96%
“…14 Male Unknown Situs inversus totalis Zhu et al, 2017 [1] 9 Female Hemivertebrae Situs inversus totalis, syringomyelia, congenital heart defect, pulmonary dysfunction, hydronephrosis Alkin et al, 2018 22 Female Unknown KS Guo et al, 2022 [9] 19 Male Idiopathic scoliosis KS, smell and hearing defects, Asthenoteratozoospermia Guo et al, 2022 [9] 37 Female Idiopathic scoliosis KS, smell and hearing defects, immature uterus Our case, 2022 2 Female Hemivertebrae Situs inversus totalis, atrial septal defect, polydactyl KS = Kartagener syndrome.…”
Section: Author Contributionsmentioning
confidence: 99%
“…The mechanism of different pathogenic genes leading to different clinical phenotypes, or even different mutations of the same pathogenic gene leading to different clinical phenotypes (Shoemark et al, 2018) is still unclear, which requires more basic research to explore. Patients with known DNAAF4 mutations tend to exhibit severe phenotypes (Tarkar et al, 2013;Guo T et al, 2022), including neonatal respiratory distress, recurrent respiratory symptoms, and infertility. In this study, the proband did not manifest neonatal respiratory distress, but exhibited complete situs inversus, chronic sinusitis, bronchiectasis, recurrent bronchitis and pneumonia, and infertility, with low level of nNO and severe pulmonary ventilation dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…But absolute infertility is occurred in female with mutations in the genes DNAAF1 and LRRC6 encoding dynein axonemal assembly factor ( Vanaken et al, 2017 ). Previous studies and reports have suggested that mutations in DNAAF4 can lead to infertility (male and female) ( Tarkar et al, 2013 ; Guo T et al, 2022 ). Therefore, we can infer that the DNAAF4 mutation caused infertility in the proband.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation